2010
DOI: 10.3324/haematol.2009.011114
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of adult acute lymphoblastic leukemia by single nucleotide polymorphism oligonucleotide microarray and comparison to pediatric acute lymphoblastic leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundDifferences in survival have been reported between pediatric and adult acute lymphoblastic leukemia. The inferior prognosis in adult acute lymphoblastic leukemia is not fully understood but could be attributed, in part, to differences in genomic alterations found in adult as compared to in pediatric acute lymphoblastic leukemia. Design and MethodsWe compared two different sets of high-density single nucleotide polymorphism array genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
8
36
1
Order By: Relevance
“…19 A recent study using single nucleotide polymorphism oligonucleotide microarray found microdeletion of 17p (TP53) in 11% of all adult precursor B-ALL. 20 We found that hypodiploidy, particularly with complete loss of chromosome 5, 7 and 17(17p), was significantly more frequent among group 1 patients and all patients with this anomaly had received alkylating agents. This finding parallels the common cytogenetic alterations reported in t-MN after alkylating chemotherapy.…”
Section: Discussionmentioning
confidence: 75%
“…19 A recent study using single nucleotide polymorphism oligonucleotide microarray found microdeletion of 17p (TP53) in 11% of all adult precursor B-ALL. 20 We found that hypodiploidy, particularly with complete loss of chromosome 5, 7 and 17(17p), was significantly more frequent among group 1 patients and all patients with this anomaly had received alkylating agents. This finding parallels the common cytogenetic alterations reported in t-MN after alkylating chemotherapy.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, there remains a substantial proportion of ALL cases that lack known cytogenetic alterations and fail therapy, and the frequency of these cases rises with increasing age. Compared with childhood leukemia, there is a lack of detailed, high-resolution genomic profiling data from adolescent and adult ALL, [95][96][97] which has a markedly inferior outcome to that of childhood ALL. The frequency of Ph þ ALL rises progressively with increasing age, but this alone does not account for the poor outcome of ALL with increasing age, and at present it is unclear whether the frequency of poorrisk mutations and expression profiles observed in pediatric ALL will be recapitulated in the adult setting.…”
Section: Future Directions For Genomic Profiling In High-risk Allmentioning
confidence: 99%
“…4,7,8 Whether the pattern of microdeletions, as ascertained by single nucleotide polymorphism (SNP) array analysis, also differs between childhood and adult BCP ALL is less well clarified because most analyses of ALL have been performed on pediatric cases. 9,10 In fact, SNP array findings in adult ALL have so far been reported in only three larger series, [11][12][13] one of which focused solely on IKZF1 deletions. 13 The two other studies 11,12 identified similar gene deletions to those found in pediatric cases, namely losses of CDKN2A, PAX5, IKZF1, ETV6, RB1, EBF1 and LEF1.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In fact, SNP array findings in adult ALL have so far been reported in only three larger series, [11][12][13] one of which focused solely on IKZF1 deletions. 13 The two other studies 11,12 identified similar gene deletions to those found in pediatric cases, namely losses of CDKN2A, PAX5, IKZF1, ETV6, RB1, EBF1 and LEF1. However, these results were based on quite small cohorts of patients, comprising 45 and 75 adult ALL patients, respectively.…”
Section: Introductionmentioning
confidence: 99%